The Cultural Meaning of Ceremonial Water in Seloliman Village as Constructing the Awareness of Care about Nature - Jenny Yudha Utama; Visi Mustika Sari; Candra Adi Wicaksono (Pancaran Pendidikan, 2018)
This research is related to belief or culture in Seloliman village, Trawas sub-district, Mojokerto regency; it is Ceremonial Water in Jolotundo Petirtaan. Clifford Geertz assumed that culture as networks did not constitute an experimental science to look for the law but it was the interpretative science to look for meaning and symbol. This study used descriptive qualitative methods in which researchers attempted to describe written or oral words from observable people or behaviour. The findings indicated that culture or belief in the modern era was still applied because a culture or belief had symbol and meaning for people who believe it.